Effect of Body Mass Index on the Outcome of Surgical Patients Receiving Extracorporeal Devices (VV ECMO, pECLA) for Respiratory Failure. Issue 3 (March 2017) - Swol, Justyna; Buchwald, Dirk; Strauch, Justus T.; Schildhauer, Thomas A.; Ull, Christopher
Introduction: To determine whether obese surgical patients are at a significant disadvantage in terms of outcomes after extracorporeal device (ECD) support, such as veno-venous extracorporeal membrane oxygenation (VV ECMO) or pumpless extracorporeal lung assist (pECLA), for respiratory failure, the relationship between body mass index (BMI) and hospital outcomes was analyzed. Methods: This retrospective study included data on patients who were supported with an ECD between January 1, 2008 and December 31, 2014. The analysis included 89 patients (74 male). Results: The median BMI was 30 kg/m 2 (19–88.5). The median duration of the ECD support was 9.0 days, with a maximum of 37.1 days. The median LOS (length of stay) in the intensive care unit (ICU) was 21 days (range 0.06–197.6). The median hospital LOS was 34.9 days (range 0.1–213.8). VV ECMO was performed 72 times, and pECLA was performed 18 times. The number of patients successfully weaned off the ECD was 54 (60.6%). Survival at the discharge from the hospital was 48.3%. Conclusions: 54 (60.6%) patients were successfully weaned off the ECD; 43 (48.3%) patients survived and were discharged from the hospital. The analysis of correlations between BMI and outcomes of surgical patients treated with ECD showed no association between BMI and mortality. Complications (especially oxygenator clotting) were not more frequent in obese and extremely obese patients. We hypothesized that patients with higher or morbid BMIs would have increased mortality after ECD support. A BMI of 30.66 kg/m 2 corresponded to the desired sensitivity and specificity to predict mortality. This finding applied only to the study group. Treatment with ECD in obese patients presents unique challenges, including percutaneous cannulation and increased staff requirements. However, based on these data, obesity should not be an exclusion criterion for ECD therapy.